CRMP2 mediates Sema3F-dependent axon pruning and dendritic spine remodeling - Ziak, Jakub; Weissova, Romana; Jeřábková, Kateřina; Janikova, Martina; Maimon, Roy; Petrasek, Tomas; Pukajova, Barbora; Kleisnerova, Marie; Wang, Mengzhe; Brill, Monika S.; Kasparek, Petr; Zhou, Xunlei; et al. (EMBO reports, 2020)
Regulation of axon guidance and pruning of inappropriate synapses by class 3 semaphorins are key to the development of neural circuits. Collapsin response mediator protein 2 (CRMP2) has been shown to regulate axon guidance by mediating semaphorin 3A (Sema3A) signaling; however, nothing is known about its role in synapse pruning. Here, using newly generated crmp2-/- mice we demonstrate that CRMP2 has a moderate effect on Sema3A-dependent axon guidance in vivo, and its deficiency leads to a mild defect in axon guidance in peripheral nerves and the corpus callosum. Surprisingly, crmp2-/- mice display prominent defects in stereotyped axon pruning in hippocampus and visual cortex and altered dendritic spine remodeling, which is consistent with impaired Sema3F signaling and with models of autism spectrum disorder (ASD). We demonstrate that CRMP2 mediates Sema3F signaling in primary neurons and that crmp2-/- mice display ASD-related social behavior changes in the early postnatal period as well as in adults. Together, we demonstrate that CRMP2 mediates Sema3F-dependent synapse pruning and its dysfunction shares histological and behavioral features of ASD.